ANALYSIS OF SUSPENDED SOLIDS CONTENT IN RICE FIELD STREAM WATER CONSUMED BY PANTE KUYUN VILLAGE COMMUNITY ACEH JAYA DISTRICT - Nurdin, Ambia; Jannah, Rauzatul; Putri, Rossalia (Transpublika Publisher, 2023)
Water is vital to life and ecosystems on Earth. It supports important ecological functions, such as providing resources for flora and fauna, regulating climate, and various biogeochemical processes that affect the environment as a whole. All living organisms, including humans, depend on water for their survival and well-being. This research is a descriptive analysis that aims to reveal the content of suspended solids in the water of rice field streams in Pante Kuyun Village. Conducted since November 2023, this research took place in Aceh Jaya District, with the analysis of suspended solids levels carried out at the Aceh Health Research and Development Center Laboratory. The research subjects included the people of Pante Kuyun Village and the water of the rice fields in the area. The sampling method was representative, where one sample was taken from the water of the Pante Kuyun Village rice field. The results showed that the level of suspended solids (TSS) in the rice paddy stream water reached 6.4 mg/L. These findings provide an important snapshot of the water quality in the area, which can serve as a foundation for further policies and actions to maintain the sustainability of the ecosystem and the health of local communities.